Magnetic write field characterization in heat-Assisted magnetic recording systems - Kampun, Prasit; Lekawat, Lertsak; Tongsomporn, Damrongsak (My University, 2020)
Magnetic write field is a critical factor in determining the quality of the magnetic write transitions, which determine the linear density (LD) limit in heat-Assisted magnetic recording (HAMR). We introduce a reversed DC band approach as a simple, no extra-hardware-Required technique in a spin-stand to assess the magnetic write field contributions, independently in an HAMR system. Heads with different distances between near-field transducer and writer pole, and media with and without soft magnetic under layer were characterized. The estimated result strongly correlates with LD and signal-To-noise ratio, which agrees with previous modeling studies. These results give insight into the head/component required to optimize the HAMR's system performance. The technique provides qualitative ranking of magnetic write fields and recording temperature, as well as laser operating current at Curie temperature for head/component designs.